Language and communication strategies for climate change engagement among Indonesian millennials and gen z - Putri, Putri Bunga Yossilia; Arifin, Muhammad Andy; Lestari, Herlina Devi; Nasrullah, Riki; Rohim, Rohim (NOTION: Journal of Linguistics, Literature, and Culture, 2025)
This study examines how language and communication strategies can influence the perception and response of Gen-Millennials and Gen-Z towards climate change issues in Indonesia. Using a quantitative survey method, data were collected from 127 respondents consisting of 77 Gen-Z and 50 Gen-Millennials, and presented concisely and structured through frequency tables and illustrative diagrams. The data analysis process was carried out through several stages, namely descriptive analysis, inferential analysis, and then interpreting the findings. The findings show that the intensity of social media use from Gen-Millennials is more often aimed at seeking information than Gen-Z which is only for entertainment, the result is that Gen-M interacts more often with climate change issues than Gen-Z, although both still consider it important. Furthermore, persuasive technical terms have the potential to increase the motivation of both generations to be directly involved in climate change action. This study highlights the need for targeted communication strategies to increase public awareness and engagement on climate change issues. These findings enrich approaches to language teaching and intercultural training, particularly in the context of environmental education, broaden understanding of intergenerational communication styles in environmental advocacy, and provide practical insights for developing impactful campaigns tailored to generational preferences, thereby contributing to the success of climate advocacy efforts in Indonesia.